The Influence of Social Support and Employment Skills on Work Readiness Among Persons with Disabilities in Gresik Regency - Aida Rahmi Aulia; Nur Cahyadi (Paradoks : Jurnal Ilmu Ekonomi, 2026)
This study aims to analyze the influence of social support and employment skills on work readiness among persons with disabilities in Gresik Regency. The research employs a quantitative approach with a causal design to examine the relationships between variables. Data were collected by distributing Likert-scale questionnaires to 66 respondents with disabilities, aged 17–25 years (within the productive age range), who had completed vocational training programs. Purposive sampling was used to select participants. The variables examined include social support, employment skills, and work readiness. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software, including tests for validity, reliability, coefficient of determination (R²), predictive relevance (Q²), effect size (f²), and hypothesis testing through path coefficients. The findings indicate that social support does not have a significant impact on work readiness for individuals with disabilities, while employment skills exert a positive and significant influence on work readiness.